Moral reasoning of college students implications for moral education - Evangelista, Francis Julius N. (2004)
The study looked into the characteristics of the moral reasoning of college students, particularly the kind of ethical orientation they use when dealing with moral issues and dilemmas. The study used a quantitative methodology, supplemented by qualitative data. Data were gathered using a researcher-made questionnaire which had an open-ended part and an objective part. Findings did not support the theory that males generally are justice-oriented and females are care-oriented. Most college students used both justice and care perspectives in dealing with various dilemmas, and it was possible to make both considerations in resolving a dilemma.